Romance tourism or female sex tourism? - Bauer, Irmgard (Elsevier, 2014)
Background: Love, sex and the female traveller: romance tourism or female sex tourism? The phenomenon of women travelling in search of relationships with local men in developing countries has been studied for the last 20 years. However, it appears little known in travel medicine. Methods: Relevant literature was found through PubMed, Science Direct, ProQuest and Google Scholar. The reference lists of selected articles identified further sources. Results: Historical records of women travellers to far-away countries abound. Then, as now, women not only searched for the erotic ‘other’ but made romance and sex the purpose of their trip. Today, increasing numbers of women travel to destinations in developing countries where sex with local men is the main attraction. This pastime raises concerns not only for the women themselves but for the local men involved as well as their sex partners and the local communities. Conclusions: Although more research is necessary, comparing the criteria that describe men travelling for sex and relationships and women travelling for sex and relationships appears to suggest that there is very little difference between the two, regardless of what the pursuit is called. Women looking for sex with local men are sex tourists, too. Recognition of this fact needs to influence the pre and post travel care of female travellers.